Differences in kinetic characteristics during countermovement jump of football players with cerebral palsy according to impairment profiles - Henríquez, Matías; Sabido, Rafael; Barbado, David; Roldan, Alba; Elvira, Jose L. L.; Yanci, Javier; Reina, Raúl (Frontiers in Physiology, 2023)
The purpose of this study was 1) to determine and compare kinetic parameters during the realization of a countermovement jump (CMJ) between footballers with cerebral palsy (CP) and non-impaired footballers, and 2) to analyze the differences in this action between different players’ impairment profiles and a group of non-impaired footballers. This study involved 154 participants comprising 121 male footballers with CP from 11 national teams and 33 male non-impaired football players recruited as the control group (CG). The footballers with CP were described according to the different impairment profiles (bilateral spasticity = 10; athetosis or ataxia = 16; unilateral spasticity = 77; minimum impairment = 18). All participants performed three CMJs on a force platform to record kinetic parameters during the test. Results: The group of para-footballers presented significantly lower values than the CG in the jump height (p < 0.01, d = -1.28), peak power (p < 0.01, d = -0.84), and the net concentric impulse (p < 0.01, d = -0.86). Concerning the pairwise comparisons between CP profiles and the CG, significant differences were found for the bilateral spasticity, athetosis or ataxia, and unilateral spasticity subgroups compared to the non-impaired players for jump height, power output, and concentric impulse of the CMJ. When comparing the minimum impairment subgroup with the CG, only significant differences were found for jump height. Footballers with minimum impairment presented higher jumping height and concentric impulse compared to those with bilateral spasticity. Also, the unilateral spasticity subgroup reports a higher jump height performance than the bilateral group. Conclusions: These results suggest that the variables related to power production during the concentric phase of the jump are crucial for the performance differences between groups with and without impairment. This study provides a more comprehensive understanding of kinetic variables that would differentiate CP and non-impaired footballers. However, more studies are necessary to clarify which parameters better differentiate among different profiles of CP. The findings could help to prescribe effective physical training programs and support the classifier’s decision-making for class allocation in this para-sport.